2020
DOI: 10.1002/jcsm.12615
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cachexia in a mouse model of oxidative stress

Abstract: Background Cancer is associated with muscle atrophy (cancer cachexia) that is linked to up to 40% of cancer-related deaths. Oxidative stress is a critical player in the induction and progression of age-related loss of muscle mass and weakness (sarcopenia); however, the role of oxidative stress in cancer cachexia has not been defined. The purpose of this study was to examine if elevated oxidative stress exacerbates cancer cachexia. Methods Cu/Zn superoxide dismutase knockout (Sod1KO) mice were used as an establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 85 publications
(207 reference statements)
3
29
1
Order By: Relevance
“…Moreover, muscle protein synthesis is one of the two major components when it comes to net protein balance while its role in CC has not been clearly understood. While our data 62 , 63 and other works 60 , 61 clearly demonstrate reduced protein anabolism in pre-clinical animal models of CC, understanding of the suppression of anabolic signaling remains incomplete. 60 , 75 The primary cellular signaling pathway of muscle growth known as Akt/mTOR signaling is an essential part of muscle protein synthesis.…”
Section: Changes In Skeletal Muscle During the Development Of CCcontrasting
confidence: 51%
See 2 more Smart Citations
“…Moreover, muscle protein synthesis is one of the two major components when it comes to net protein balance while its role in CC has not been clearly understood. While our data 62 , 63 and other works 60 , 61 clearly demonstrate reduced protein anabolism in pre-clinical animal models of CC, understanding of the suppression of anabolic signaling remains incomplete. 60 , 75 The primary cellular signaling pathway of muscle growth known as Akt/mTOR signaling is an essential part of muscle protein synthesis.…”
Section: Changes In Skeletal Muscle During the Development Of CCcontrasting
confidence: 51%
“…Previous studies have reported that both in vivo and in vitro models of CC can lead to impaired mitochondrial function including reduced respiratory capacity, ATP production, and elevated reactive oxygen species (ROS) emission. 43 , 63 , 87 , 88 However, our recent findings reveal mitochondrial ROS generation and mitochondrial oxidative stress precedes the development of CC in LLC tumor-bearing mice. 84 Elevated ROS emission is associated with impaired mitochondrial quality control (MQC) mechanisms including mitochondrial dynamics (fusion and fission) and autophagy (mitophagy).…”
Section: Changes In Skeletal Muscle During the Development Of CCmentioning
confidence: 82%
See 1 more Smart Citation
“…Evidence from preclinical models show that mitochondrial ROS emissions increase with cancer cachexia and are accompanied by increased markers of oxidative stress [35,138,139,150,151]. In contrast to these findings, some studies have reported decreased markers of muscle oxidative stress, and that exacerbated oxidative stress does not accentuate cancer cachexia [146,152]. Perhaps one explanation for this discrepancy between experimental findings can be explained by evidence of the time course of mitochondrial dysfunction.…”
Section: Mitochondria and Cancer Cachexiamentioning
confidence: 99%
“…The algorithm we proposed can be considered more comprehensive in respect to the others previously described. In the vast majority, only the motor system (most frequently one nerve) [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] or only the sensory or mixed nerves [ 12 , 44 , 45 , 46 , 47 ] were tested. A few groups tested both the motor and sensory systems, but none of the tests were performed at the same time as EMG recordings [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%